Modelling the Fiscal Reaction Functions of the GIPS Based on State-Varying Thresholds - Gabriella Deborah Legrenzi; Costas Milas (Center for Economic Studies and ifo Institute (CESifo), 2013)
We extend previous literature on fiscal policy sustainability by introducing non-linear fiscal reaction functions with endogenously estimated state-varying thresholds to capture the behaviour of fiscal policy authorities during good and bad times. These thresholds vary with the level of debt, the economic cycle and an index of financial pressure.
Keywords: C20; H30; H50; 330; debt sustainability; fiscal reaction function; state-varying threshold